Factors and Psychological Impact of Hajj Pilgrims Failing to Depart in 2024 Semarang City - Nurul Mafaza; Abdul Sattar; Abdul Rozaq; Hasyim Hasanah; Muh. Syahri Romadhon (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
In 2024, a number of pilgrims in Semarang City experienced failure in departure, which has the potential to cause psychological impacts, such as stress, anxiety, and depression. This failure can be influenced by various factors, including regulatory, health, and administrative. Therefore, this study aims to explore the psychological experiences of pilgrims who failed to depart in 2024 in Semarang City, as well as identify the main factors that led to their failure to depart. This study utilizes a qualitative method with a phenomenological approach to uncover the casual factors of the failure to depart, and a quantitative method to examine the impact of the failute to depart. The research subjects were selected through purposive sampling technique, with a total of 20 pilgrims who experienced departure failure as informants. Data related to causal factors were collected through in-depth interviews, observation, and documentation, then analyzed using the phenomenological analysis method. Meanwhile, the psychological impact was collected through the DASS-42 questionnaire. The results showed that the main factors for failure to depart include financial instability, government policies, health problems, shar'i excuses, and personal reasons. The psychological impact felt by pilgrims is depression, disappointment, and stress with normal to very severe levels. This study reveals that failure to go on Hajj has a significant psychological impact on pilgrims. Therefore, psychological assistance and policy improvements are needed so that pilgrims who experience failure still get adequate emotional support.